Soft magnetic alloys and magnetic components.

By forming a Co-enhanced area in the soft magnetic alloy, the concentration of Co is improved, and the problem of easy corrosion of existing soft magnetic alloys is solved, and the high corrosion protection performance is improved.

JP7658782B2Active Publication Date: 2025-04-08TDK CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021061031
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-04-08
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Existing soft magnetic alloys are prone to corrosion in storage and use environments, such as rust, and lack high corrosion protection performance.

Method used

A soft magnetic alloy is used, and its inner region contains an alloy of Fe and Co., and the surface region forms a Co-enhanced region, with a higher concentration of Co concentration than the inner region, and a higher concentration of Co-enhanced region than 1.2.

Benefits of technology

It effectively suppresses rust in the immersion environment and improves the corrosion protection performance of soft magnetic alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658782000011
    Figure 0007658782000011
  • Figure 0007658782000012
    Figure 0007658782000012
  • Figure 0007658782000013
    Figure 0007658782000013
Patent Text Reader

Abstract

To provide a soft magnetic alloy having high corrosion resistance and a magnetic component using the soft magnetic alloy.SOLUTION: A soft magnetic alloy includes an internal region having a soft magnetic alloy composition containing Fe and Co, and a Co-enriched region that exists closer to the surface than the internal region and has a higher Co concentration than the internal region, and the Co concentration in the Co-enriched region is greater than 1.2.SELECTED DRAWING: Figure 3A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a soft magnetic alloy and a magnetic part using the soft magnetic alloy. [Background technology]

[0002] Soft magnetic alloys such as those shown in Patent Documents 1 to 3 are known as magnetic materials used in various magnetic parts such as inductors. These soft magnetic alloys have a higher saturation magnetic flux density Bs than ferrite materials and have good soft magnetic properties. However, soft magnetic alloys may become corroded, such as rusting, depending on the storage conditions and usage environment, so there is a demand for improved corrosion resistance. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2009-293099 A [Patent Document 2] JP 2007-231415 A [Patent Document 3] JP 2014-167139 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a soft magnetic alloy having high corrosion resistance, and a magnetic component using the soft magnetic alloy. [Means for solving the problem]

[0005] In order to achieve the above object, the soft magnetic alloy according to the present invention comprises: an inner region having a soft magnetic alloy composition including Fe and Co; A Co-enriched region is present on the surface side of the inner region and has a higher Co concentration than the inner region, The degree of Co enrichment in the Co-enriched region is greater than 1.2.

[0006] As a result of extensive research, the present inventors have found that a soft magnetic alloy having the above-mentioned characteristics suppresses rusting when immersed in water and improves corrosion resistance.

[0007] Preferably, the Co-enriched region is a metallic phase.

[0008] Preferably, the soft magnetic alloy has an amorphous degree of 85% or more.

[0009] The soft magnetic alloy may be in the form of a thin ribbon or a powder.

[0010] The application of the soft magnetic alloy of the present invention is not particularly limited, and it can be applied to various magnetic parts such as coil parts such as inductors, filters, antennas, etc. Among the above applications, the soft magnetic alloy of the present invention is suitable as a material for the magnetic core in coil parts and the like. [Brief description of the drawings]

[0011] [Figure 1A] FIG. 1A is an enlarged cross-sectional view of a main part of a soft magnetic alloy 1 according to one embodiment of the present invention. [Figure 1B] FIG. 1B is an example of an enlarged cross-sectional view of a main part of a soft magnetic alloy 1a according to one embodiment of the present invention. [Figure 2A] FIG. 2A is an example of a chart obtained by X-ray crystal structure analysis. [Figure 2B] FIG. 2B is an example of a pattern obtained by profile fitting the chart shown in FIG. 2A. [Figure 3A] FIG. 3A is an example of a graph obtained by performing a line analysis using EDX along the measurement line LM shown in FIG. 1A. [Figure 3B] FIG. 3B is an example of a graph obtained by performing a line analysis using EDX along the measurement line LMa shown in FIG. 1B. [Figure 4A]FIG. 4A is a cross-sectional view showing a soft magnetic alloy 1b according to one embodiment of the present invention. [Figure 4B] FIG. 4B is an enlarged cross-sectional view of region IVB shown in FIG. 4A. [Figure 5A] FIG. 5A is an example of an EELS image of the soft magnetic alloy 1 shown in FIG. 1A. [Figure 5B] FIG. 5B is an example of an EELS image of the soft magnetic alloy 1a shown in FIG. 1B. [Figure 5C] FIG. 5C is an example of a STEM image of the soft magnetic alloy 1b shown in FIG. 4A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the present invention will be described in detail based on the embodiments shown in the drawings.

[0013] The soft magnetic alloy 1 of the present embodiment may have a ribbon shape, a powder shape, or other block shape, and the shape of the soft magnetic alloy 1 is not particularly limited. The dimensions of the soft magnetic alloy 1 are also not particularly limited. For example, when the soft magnetic alloy 1 is in a ribbon shape, the thickness of the ribbon may be 15 μm to 100 μm, and when the soft magnetic alloy 1 is in a powder shape, the average particle size of the soft magnetic alloy powder may be 0.5 μm to 150 μm, and is preferably 0.5 μm to 25 μm.

[0014] The above average particle size can be measured by various particle size analysis methods such as laser diffraction, but it is preferable to measure it using a particle image analyzer Morphologi G3 (manufactured by Malvern Panatical). In Morphologi G3, soft magnetic alloy powder is dispersed by air, the projected area of ​​the particles constituting the powder is measured, and the particle size distribution based on the circular equivalent diameter is obtained from the projected area. Then, in the obtained particle size distribution, the particle size at which the cumulative relative frequency based on volume or number is 50% can be calculated as the average particle size. When soft magnetic alloy 1 is included in a magnetic core, the average particle size of soft magnetic alloy 1 (powder) can be calculated by measuring the circular equivalent diameter of the particles included in the cross section by observing the cross section using an electron microscope (SEM, STEM, etc.).

[0015] Fig. 1A is an enlarged cross-sectional view of the vicinity of the surface of the soft magnetic alloy 1. As shown in Fig. 1A, the soft magnetic alloy 1 has an inner region 2 and a Co-enriched region 11 located closer to the surface of the soft magnetic alloy 1 than the inner region 2. In this embodiment, the "inner side" means a side closer to the center of the soft magnetic alloy 1, and the "surface side" or "outer side" means a side farther from the center of the soft magnetic alloy 1.

[0016] (internal area 2) The internal region 2 is a base portion of the soft magnetic alloy 1 that occupies at least 90 vol % or more of the volume of the soft magnetic alloy 1. Therefore, the average composition of the soft magnetic alloy 1 can be regarded as the composition of the internal region 2, and the crystal structure of the soft magnetic alloy 1 can be regarded as the crystal structure of the internal region 2. The volume ratio of the internal region 2 described above can be replaced with an area ratio, and the internal region 2 occupies at least 90% or more of the cross-sectional area of ​​the soft magnetic alloy 1.

[0017] The inner region 2 (i.e., the soft magnetic alloy 1) has a soft magnetic alloy composition containing Fe and Co, and the specific alloy composition is not particularly limited. For example, the inner region 2 can be a crystalline soft magnetic alloy such as an Fe-Co alloy, an Fe-Co-V alloy, an Fe-Co-Si alloy, or an Fe-Co-Si-Al alloy. Furthermore, the inner region 2 preferably contains P, and examples of crystalline soft magnetic alloys containing P include an Fe-Co-Si-P alloy and an Fe-Co-Si-P-Cr alloy. By containing P in the inner region 2, Co is easily concentrated at the outer edge of the inner region 2.

[0018] Moreover, from the viewpoint of reducing the coercive force, the inner region 2 preferably has an amorphous or nanocrystalline alloy composition. Examples of amorphous or nanocrystalline soft magnetic alloys include Fe-Co-PC based alloys, Fe-Co-B based alloys, and Fe-Co-B-Si based alloys. More specifically, the inner region 2 has a composition formula ((Fe (1-( α + β )) CoαNiβ) 1- γX1γ)(1-(a+b+c+d+e)) B a P b S c C d Cr e By having the above composition, an amorphous, heteroamorphous, or nanocrystalline crystal structure is easily obtained.

[0019] In the above composition formula, B is boron, P is phosphorus, C is carbon, and X1 is one or more elements selected from Ti, Zr, Hf, Nb, Ta, Mo, W, Al, Ga, Ag, Zn, S, Ca, Mg, V, Sn, As, Sb, Bi, N, O, Au, Cu, rare earth elements, and platinum group elements. Rare earth elements include Sc, Y, and lanthanides, and platinum group elements include Ru, Rh, Pd, Os, Ir, and Pt. In addition, α, β, γ, a, b, c, d, and e are atomic ratios, and these atomic ratios preferably satisfy the following requirements.

[0020] Fe , the total amount of Co and Ni The Co content (α) is 0.005≦α≦0.700, may be 0.010≦α≦0.600, may be 0.030≦α≦0.600, or may be 0.050≦α≦0.600. When α is within the above range, Bs and corrosion resistance are improved. From the viewpoint of improving Bs, it is preferable that 0.050≦α≦0.500. The larger α is, the more corrosion resistance tends to be improved, but if α is too large, Bs is likely to decrease.

[0021] Also, Fe , the total amount of Co and Ni The Ni content (β) relative to the total weight is 0≦β≦0.200. That is, Ni may not be contained, or may be 0.005≦β≦0.200. From the viewpoint of improving Bs, it may be 0≦β≦0.050, 0.001≦β≦0.050, or 0.005≦β≦0.010. The larger β is, the more the corrosion resistance tends to improve, but if β is too large, Bs decreases.

[0022] X1 may be contained as an impurity or may be added intentionally. The content of X1 (γ) is 0≦γ<0.030. That is, less than 3.0% of the total content of Fe, Co and Ni may be substituted with X1.

[0023] Furthermore, when the sum of the atomic ratios of the elements constituting the soft magnetic alloy is 1, the atomic ratio (1-(a+b+c+d+e)) of the total content of Fe, Co, Ni, and X1 is preferably 0.720≦(1-(a+b+c+d+e))≦0.950, and more preferably 0.780≦(1-(a+b+c+d+e))≦0.890. By satisfying this requirement, Bs is easily improved. In addition, by satisfying 0.720≦(1-(a+b+c+d+e))≦0.890, it is easy to obtain an amorphous structure.

[0024] a is the atomic ratio of B, and is preferably 0≦a≦0.200, and from the viewpoint of improving Bs, more preferably 0≦a≦0.150.

[0025] b is the atomic ratio of P, and is preferably 0≦b≦0.100. In other words, P does not have to be contained, and from the viewpoint of simultaneously improving Bs and corrosion resistance, it is more preferable that 0.001≦b≦0.100, further preferably that 0.005≦b≦0.080, and particularly preferably that 0.005≦b≦0.050.

[0026] c is the atomic ratio of Si, and is preferably 0≦c≦0.150. That is, Si does not have to be contained, and from the viewpoint of simultaneously improving Bs and corrosion resistance, it is more preferable that 0.001≦b≦0.070.

[0027] d is the atomic ratio of C, and is preferably 0≦d≦0.050. In other words, C does not have to be contained, and from the viewpoint of simultaneously improving Bs and corrosion resistance, it is more preferable that 0≦d≦0.020.

[0028] e is the atomic ratio of Cr, and is preferably 0≦e≦0.050. That is, from the viewpoint of improving Bs, Cr does not have to be contained, and from the viewpoint of improving both Bs and corrosion resistance, it is more preferable that 0.001≦d≦0.020.

[0029] The composition of the inner region 2 (i.e., the composition of the soft magnetic alloy 1) can be analyzed, for example, by inductively coupled plasma emission spectrometry (ICP). In this case, if it is difficult to determine the amount of oxygen by ICP, impulse heating melting extraction method can be used in combination. In addition, if it is difficult to determine the amount of carbon and sulfur by ICP, infrared absorption method can be used in combination.

[0030] In addition to ICP, composition analysis may be performed using EDX (energy dispersive X-ray analysis) or EPMA (electron probe microanalyzer) attached to an electron microscope. For example, for the soft magnetic alloy 1 contained in a magnetic core having a resin component, composition analysis using ICP may be difficult. In this case, composition analysis may be performed using EDX or EPMA. In addition, if detailed composition analysis is difficult using any of the above methods, composition analysis may be performed using 3DAP (three-dimensional atom probe). When 3DAP is used, the composition of the soft magnetic alloy 1, that is, the inner region 2, can be measured while excluding the effects of resin components and surface oxidation in the analyzed region. This is because 3DAP allows the average composition to be measured by setting a small region (for example, a region of Φ20 nm × 100 nm) inside the soft magnetic alloy 1.

[0031] When a line analysis is performed on a cross section near the surface of the soft magnetic alloy 1 using EDX or EELS (electron energy loss spectroscopy), the internal region 2 can be recognized as a region where the Fe concentration and Co concentration are stable (see FIG. 3A). For example, the average composition obtained by mapping analysis in the internal region 2 can be regarded as the composition of the soft magnetic alloy 1. In this case, the mapping analysis is performed using EDX or EELS, and the measurement location is a region 100 nm or more away from the surface of the soft magnetic alloy 1 in the depth direction (corresponding to the internal region 2), and the measurement field of view may be a range of about 256 nm × 256 nm.

[0032] The crystal structure of the inner region 2 (i.e., the crystal structure of the soft magnetic alloy 1) can be crystalline, nanocrystalline, or amorphous, and is more preferably amorphous. In other words, the degree of amorphization X of the inner region 2 (i.e., the degree of amorphization X of the soft magnetic alloy 1) is preferably 85% or more. A crystal structure with a degree of amorphization X of 85% or more is a structure that is mostly composed of amorphous material, or a structure that is composed of heteroamorphous material. Here, a structure that is composed of heteroamorphous material means a structure in which a small amount of crystals are present in the amorphous material. That is, in this embodiment, the "amorphous crystal structure" means a crystal structure with a degree of amorphization X of 85% or more, which may contain crystals within a range that satisfies the degree of amorphization X.

[0033] In the case of a heteroamorphous structure, the average crystal grain size of the crystals present in the amorphous material is preferably 0.1 nm or more and 10 nm or less. In the present embodiment, the term "nanocrystal" refers to a crystal structure in which the degree of amorphousness X is less than 85% and the average crystal grain size is 100 nm or less (preferably 3 nm to 50 nm), and the term "crystalline" refers to a crystal structure in which the degree of amorphousness X is less than 85% and the average crystal grain size exceeds 100 nm.

[0034] The degree of amorphization X can be measured by X-ray crystal structure analysis using XRD. Specifically, the soft magnetic alloy 1 according to this embodiment is subjected to 2θ / θ measurement by XRD to obtain a chart as shown in Fig. 2A. In this case, the measurement range of the diffraction angle 2θ is set to a range in which a halo derived from the amorphous phase can be confirmed, and is preferably set to, for example, a range of 2θ=30° to 60°.

[0035] Next, profile fitting is performed on the chart shown in Fig. 2A using the Lorentz function shown in the following formula (2). In this profile fitting, it is preferable to set the error between the integrated intensity actually measured by XRD and the integrated intensity calculated using the Lorentz function to within 1%. By this profile fitting, a crystalline component pattern α showing the crystalline scattering integrated intensity Ic as shown in Fig. 2B is obtained. c , amorphous component pattern α showing amorphous scattering integrated intensity Ia a , and the combined pattern α c+a The degree of amorphism X can be calculated by introducing the crystalline scattering integrated intensity Ic and the amorphous scattering integrated intensity Ia obtained here into the following formula (1).

[0036] X = 100 - (Ic / (Ic + Ia) × 100) ... (1) Ic: Crystalline scattering integrated intensity Ia: Amorphous scattering integrated intensity

number

[0037] The method for measuring the degree of amorphousness X is not limited to the above-mentioned method using XRD, and it may be measured by EBSD (crystal orientation analysis) or electron beam diffraction.

[0038] (Co enriched area 11) The Co-enriched region 11 is a region in which the concentration of Co is higher than that of the above-mentioned inner region 2. In this embodiment, the Co-enriched region 11 is preferably an amorphous metal phase that is continuous with the inner region 2, and covers at least a part of the outer periphery of the inner region 2. In the cross section of the soft magnetic alloy 1, the coverage of the Co-enriched region 11 with respect to the inner region 2 is not particularly limited, but can be, for example, 50% or more, and more preferably 80% or more.

[0039] The presence or absence of the Co-enriched region 11 and its coverage can be confirmed by observing a cross section near the surface of the soft magnetic alloy 1 with a STEM (scanning transmission electron microscope) or a TEM (transmission electron microscope) and performing a mapping analysis using EDX or EELS. For example, the image (EELS image) shown in FIG. 5A is an example of a mapping analysis result by EELS. The EELS image shows the distribution of Co, and the shading of Co is represented by light and dark contrast. In FIG. 5A, the inner region 2 can be recognized as a region where there is almost no shading in the concentration distribution of Co. And, at the edge of the inner region 2, the contrast becomes bright, and it can be seen that the Co concentration is higher than that of the inner region 2. This region with a high Co concentration is the Co-enriched region 11, and the presence or absence of the Co-enriched region 11 can be confirmed by the EELS image of Co.

[0040] The average thickness t1 of the Co-enriched region 11 determined by the mapping analysis is preferably 0.3 nm or more. The upper limit of t1 is not particularly limited and can be, for example, 30.0 nm or less. By increasing t1 within this preferred range, better results can be obtained in terms of corrosion resistance. Note that the average thickness t1 is preferably calculated by measuring the thickness of the Co-enriched region 11 at at least three or more points by changing the measurement field of view.

[0041] As described above, the thickness of the Co-rich region 11 may be extremely thin, and therefore, when identifying the Co-rich region 11, it is preferable to use not only mapping analysis but also line analysis. M3A is a schematic diagram illustrating the results of line analysis along the line 10, where the vertical axis represents the detection intensity of each element (i.e., the intensity of characteristic X-rays) and the horizontal axis represents the distance (depth) from the outermost surface 10. As shown in Fig. 3A, in the line analysis results, a peak where the Co concentration is high can be confirmed at the edge of the internal region 2 where the concentrations of Fe and Co are stable, and the location where this Co peak exists is the Co-enriched region 11. In other words, in the Co-enriched region 11, a maximum value of Co concentration exists, and the presence or absence of the above-mentioned peak can be used to confirm the presence or absence of the Co-enriched region 11.

[0042] As described above, the Co-enriched region 11 where the peak exists is preferably a metallic phase. The phase state of the Co-enriched region 11 can be confirmed by the above-mentioned line analysis, mapping analysis, or analysis using an EELS (electron energy loss spectroscopy) detector attached to a STEM or TEM. For example, by analyzing a spectrum obtained by EELS, the ratio of oxide Co and metal Co in the Co-enriched region 11 can be calculated, and when the ratio of metal Co is higher than that of oxide Co, the Co-enriched region 11 is defined as a metallic phase. In addition, when an oxide layer (such as the SB oxide layer 12, Fe oxide layer 13, and coating layer 20 described later) exists outside the Co-enriched region 11, the detection intensity of oxygen in the Co-enriched region 11 is lower than that of the oxide layer in the mapping analysis or line analysis. By such an analysis, it can be seen that the Co-enriched region 11 is a metallic phase.

[0043] In this embodiment, the degree of Co enrichment in the Co-enriched region 11 is calculated by the Co substance ratio (C Co ) to the Co-enriched region 11 (C11 Co ) ratio (C11 Co / C2 Co ) The Co concentration is preferably more than 1.20 and is preferably 1.50 or more. The upper limit of the Co concentration is not particularly limited, and may be, for example, 20 or less.

[0044] If a soft magnetic alloy consisting of an inner region 2 that does not form a Co-enriched region 11 is taken as a reference alloy, the corrosion resistance of the soft magnetic alloy 1 of this embodiment tends to improve as the Co concentration increases compared to the reference alloy. In other words, there is a positive correlation between the Co concentration and the corrosion resistance. In addition, when the inner region 2 of the soft magnetic alloy 1 contains a predetermined amount of P, the Co concentration tends to increase, and the corrosion resistance tends to be further improved.

[0045] C2 used to calculate Co concentration Co and C11 Co is measured by component analysis using EELS. Co is the ratio of the amount of Co to the total amount of Fe and Co detected in the inner region 2, and is calculated by analyzing the EELS spectrum. Co is the ratio of the amount of Co to the total of Fe and Co detected in the Co-enriched region 11. That is, the ratio of the amount of Co in each region is expressed as Co / (Fe+Co), and the denominator is (Fe+Co) to eliminate the influence of impurities (such as elements mixed in during the preparation of the measurement sample). Note that the resolution in this analysis is preferably set to 0.5 nm or less, and C2 Co is preferably measured at a location having a depth of 0.2 μm or more from the outermost surface 10 toward the inside of the soft magnetic alloy 1. The Co concentration degree is preferably calculated as an average value by performing the above measurement in at least five or more visual fields.

[0046] In the Co-enriched region 11, Co is detected as a main constituent element, and other elements constituting the inner region 2, such as Fe, are also contained. In the Co-enriched region 11, other elements may be enriched in the same manner as the enrichment of Co, such as P. In this case, in the mapping analysis or line analysis, a high concentration region of P may be observed so as to overlap with a region with a high concentration of Co in the depth direction of the soft magnetic alloy 1.

[0047] As described above, the soft magnetic alloy 1 has a characteristic surface layer structure including the Co-enriched region 11. In particular, in this embodiment, as shown in Fig. 1A and Fig. 3A, the Co-enriched region 11 is located on the outermost surface side and constitutes the outermost surface 10 of the soft magnetic alloy 1. However, outside the Co-enriched region 11, other surface layer structures may be present.

[0048] 1B, an Sb-oxide layer 12 containing Si and / or B may be formed to cover the surface side of a Co-enriched region 11. The Sb-oxide layer 12 is a region in which the concentration of at least one element selected from Si and B is higher than that of the inner region 2, and either Si or B, or both Si and B, are enriched.

[0049] In fact, Fig. 5B is an example of an EELS image of the soft magnetic alloy 1a shown in Fig. 1B, and all three EELS images shown in Fig. 5B are the results of measuring the same location. In the EELS image (center: BK) of B in Fig. 5B, the contrast is brighter on the surface side than the Co-enriched region 11 where Co is concentrated, and it can be confirmed that the concentration of B in this location is higher than that of the internal region 2 and the Co-enriched region 11. In the case of Fig. 5B, this region with a high B concentration is the SB oxide layer 12.

[0050] The SB oxide layer 12 may be generated during the formation of the Co-enriched region 11 when the internal region 2 contains Si and / or B, and is preferably an amorphous oxide phase. Furthermore, the average thickness t2 of the SB oxide layer 12 is preferably 0.5 nm or more. The upper limit of t2 is not particularly limited and can be, for example, 30 nm or less.

[0051] In addition, an Fe oxide layer 13 containing Fe may be formed outside the Co-enriched region 11. This Fe oxide layer 13 may be formed together with the Co-enriched region 11 in the process of forming the Co-enriched region 11, and the Fe concentration in the Fe oxide layer 13 is higher than that in the Co-enriched region 11 and the internal region 2. As shown in FIG. 1B , when the SB oxide layer 12 is present, the Fe oxide layer 13 is preferably located closer to the surface than the SB oxide layer 12, and further preferably has a higher crystallization area ratio than the SB oxide layer 12.

[0052] In fact, in the EELS image of Fe in FIG. 5B (right side: Fe-L), the contrast is brighter on the surface side than the SB oxide layer 12, and it can be confirmed that there is a region with high Fe concentration on the outermost surface of the soft magnetic alloy 1a. In FIG. 5B, this region is the Fe oxide layer 13, and the Fe oxide layer 13 constitutes the outermost surface 10 of the soft magnetic alloy 1a. In this embodiment, the average thickness t3 of the Fe oxide layer 13 is preferably 1 nm or more. The upper limit of t3 is not particularly limited and can be, for example, 50 nm or less.

[0053] FIG. 3B shows the measurement line L M 5A is a graph showing a simulated result of EDX line analysis along a. When the SB oxide layer 12 exists, as shown in FIG. 3B, a peak of Si or / and B is observed on the surface side of the Co peak, and the detection intensity of oxygen is high so as to overlap with the peak of Si or / and B. When the Fe oxide layer 13 exists on the surface side of the SB oxide layer 12, a peak of Fe can be confirmed on the surface side of the Si or / and B peak. Thus, the presence or absence of the SB oxide layer 12 or the Fe oxide layer 13 can be confirmed by line analysis using EDX or EELS, and can also be confirmed by mapping analysis as shown in FIG. 5B.

[0054] Also, as in the soft magnetic alloy 1b shown in FIG. 4A and FIG. 4B, an insulating coating layer 20 may be formed on the outside of the Co-enriched region 11. The coating layer 20 is a coating formed by a surface treatment such as coating after the formation of the Co-enriched region 11, and its average thickness is preferably 5 nm to 100 nm, more preferably 50 nm or less. In other words, when the coating layer 20 is formed, the outermost surface 10 of the soft magnetic alloy 1b is composed of the coating layer 20, and the coating layer 20 is located closer to the surface side of the soft magnetic alloy 1b than the Co-enriched region 11, the SB oxide layer 12, and the Fe oxide layer 13. In fact, FIG. 5C is an example of a STEM image of the soft magnetic alloy 1b shown in FIG. 4A. In the STEM image, a bright contrast area can be confirmed on the outermost surface 10 of the soft magnetic alloy 1b, and this area is the coating layer 20.

[0055] Thus, the surface layer structure of the soft magnetic alloy 1 may include other layers (such as the SB oxide layer 12, the Fe oxide layer 13, and the coating layer 20) in addition to the Co-enriched region 11. Even if other layers are present, the Co-enriched region 11 is present on the side in contact with the internal region 2. The perpendicular distance d1 (see FIGS. 1B and 4B) from the outermost surface to the Co-enriched region 11 is preferably 200 nm or less, more preferably 100 nm or less, and even more preferably 50 nm or less. In particular, when the coating layer 20 is not present and the outermost surface 10 is composed of the SB oxide layer 12 or the Fe oxide layer 13, the perpendicular distance d1 is preferably 30 nm or less, and more preferably 20 nm or less.

[0056] In addition, it is preferable to prepare a measurement sample for analyzing the Co-enriched region 11 by a microsampling method using a FIB (focused ion beam). For example, a Pt film is formed by sputtering on the outermost surface 10 of the soft magnetic alloy 1 to a thickness of about 30 nm for surface protection during processing, and then a range of about 2 μm deep from the outermost surface is cut out by FIB to obtain a thin sample. The thin sample is then processed to reduce the thickness in the direction perpendicular to the depth direction to 20 nm or less. This thin sample can be used as a measurement sample for TEM or HRTEM observation.

[0057] A method for producing the soft magnetic alloy 1 according to this embodiment will be described below.

[0058] The base portion (internal region 2) of the soft magnetic alloy 1 can be produced by various melting methods, but is preferably produced by a method of quenching molten metal (molten metal). This is because quenching makes it easier to obtain an amorphous soft magnetic alloy 1. For example, a ribbon-shaped soft magnetic alloy 1 can be produced by a single roll method, and a powder-shaped soft magnetic alloy 1 can be produced by an atomization method. In the following, a method of producing a soft magnetic alloy ribbon by the single roll method and a method of producing a soft magnetic alloy powder by a gas atomization method as an example of an atomization method will be described.

[0059] In the single roll method, first, raw materials (pure metals, etc.) of each element constituting the soft magnetic alloy 1 are prepared and weighed to obtain the desired alloy composition. Then, the raw materials of each element are melted to prepare a master alloy. The melting method for preparing the master alloy is not particularly limited, and may be, for example, a method of melting by high-frequency heating in a chamber with a predetermined degree of vacuum.

[0060] Next, the above-mentioned mother alloy is heated to melt, and a molten metal is obtained. The temperature of the molten metal may be set in consideration of the melting point of the target alloy composition, and may be, for example, 1200 to 1600°C. In the single roll method, the molten metal is supplied to a cooled rotating roll using a nozzle or the like, and a soft magnetic alloy ribbon is produced in the direction of rotation of the roll. At this time, the thickness of the obtained ribbon can be adjusted by controlling the rotation speed of the roll, the gap between the nozzle and the roll, the temperature of the molten metal, and the like. In addition, the temperature and rotation speed of the roll may be set under conditions that make the soft magnetic alloy easily amorphous, and for example, the roll temperature is preferably 20 to 30°C, and the rotation speed is preferably 20 to 30 m / sec. The atmosphere in the chamber is not particularly limited, and may be, for example, an air atmosphere or an inert gas atmosphere.

[0061] In the gas atomization method, molten metal at 1200 to 1600°C is obtained in the same manner as in the single roll method, and then the molten metal is sprayed in a chamber to produce powder. Specifically, the molten metal is discharged from a discharge port toward a cooling section in a chamber, and high-pressure gas is sprayed toward the discharged dripping molten metal. The dripping molten metal is scattered in the chamber by the spray of high-pressure gas, and then collides with a cooling section (cooling water) to be rapidly cooled and solidified, becoming soft magnetic alloy powder. The particle shape of the soft magnetic alloy powder obtained by this gas atomization method is usually spherical, and the average circularity of the soft magnetic alloy powder is preferably 0.8 or more, more preferably 0.9 or more, and even more preferably 0.95 or more.

[0062] As the high pressure gas, it is preferable to use an inert gas such as nitrogen gas, argon gas, or helium gas, or a reducing gas such as an ammonia decomposition gas, and the pressure at which the high pressure gas is injected is preferably 2.0 MPa or more and 10 MPa or less. The amount of molten metal injected is preferably 0.5 kg / min or more and 4.0 kg / min or less. In the gas atomization method, the particle size and shape of the soft magnetic alloy powder can be adjusted by the ratio of the pressure of the high pressure gas to the amount of molten metal injected.

[0063] After obtaining a ribbon or powder of soft magnetic alloy as described above, the soft magnetic alloy is heat-treated at a low temperature in an oxygen concentration atmosphere under a predetermined pressure state, thereby forming the Co-enriched region 11.

[0064] Specifically, the holding temperature during the heat treatment is preferably a temperature at which the soft magnetic alloy does not crystallize, for example, 200°C to 400°C is preferable, and 200°C to 300°C is more preferable. The temperature holding time is preferably 0.5 hours to 3.0 hours. The oxygen concentration in the heating furnace is preferably 20 ppm to 2000 ppm, and more preferably 100 ppm to 1000 ppm. Furthermore, while controlling the oxygen concentration as described above, the heating furnace is made positive pressure by introducing an inert gas such as argon gas or nitrogen gas, and the gauge pressure in the heating furnace is preferably 0.15 kPa to 0.50 kPa, and more preferably 0.30 kPa to 0.45 kPa. The gauge pressure means the pressure obtained by subtracting the atmospheric pressure from the absolute pressure (pressure when an absolute vacuum is 0 Pa).

[0065] By carrying out the heat treatment under such conditions, a Co-rich region 11 having a predetermined characteristic is formed on the surface layer side of the soft magnetic alloy 1. Furthermore, when the soft magnetic alloy 1 contains Si and / or B, the above heat treatment may form an Sb oxide layer 12, and depending on the heat treatment conditions, an Fe oxide layer 13 may be formed. Note that when the soft magnetic alloy 1 is to be crystalline or nanocrystalline (i.e., when the degree of amorphization X is less than 85%), a pre-process heat treatment for controlling crystallinity may be carried out before carrying out the heat treatment for forming the above-mentioned Co-rich region 11.

[0066] When forming the coating layer 20 as shown in FIG. 4A and FIG. 4B, after forming the Co-enriched region 11 by the above-mentioned heat treatment, a coating formation treatment such as phosphate treatment, mechanical alloying treatment, silane coupling treatment, hydrothermal synthesis, etc. may be performed. The types of the coating layer 20 to be formed include phosphate, silicate, soda-lime glass, borosilicate glass, lead glass, aluminosilicate glass, borate glass, sulfate glass, etc. Examples of the phosphate include magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, cadmium phosphate, etc., and examples of the silicate include sodium silicate, etc. When the coating layer 20 is formed, an improvement in the withstand voltage of the magnetic core including the soft magnetic alloy 1 can be expected.

[0067] The above steps provide a soft magnetic alloy 1 having a predetermined Co-enriched region 11. The soft magnetic alloy 1 of this embodiment can be applied to various magnetic components such as coil components such as inductors, filters, and antennas, and is particularly preferably applied to magnetic cores in coil components such as inductors. The magnetic core containing the soft magnetic alloy 1 may contain a resin component, or the magnetic core may be formed by mixing the soft magnetic alloy 1 with other magnetic particles.

[0068] (Summary of the embodiment) In the soft magnetic alloy 1 of the present embodiment, a Co-enriched region 11 having a predetermined characteristic is formed outside an internal region 2 having a soft magnetic alloy composition containing Fe and Co, and the Co enrichment degree in the Co-enriched region 11 exceeds 1.20. By having such a characteristic, rusting of the soft magnetic alloy 1 when it is immersed in water can be suppressed, and the corrosion resistance can be improved.

[0069] Furthermore, by forming the Co-enriched regions 11 in the amorphous soft magnetic alloy 1 having a degree of amorphousness of 85% or more, the corrosion resistance of the soft magnetic alloy 1 can be further improved while ensuring a high saturation magnetic flux density Bs.

[0070] Although the embodiment of the present invention has been described above, the present invention is not limited to the above-mentioned embodiment, and various modifications can be made within the scope of the present invention. EXAMPLES

[0071] The present invention will be described in more detail below with reference to specific examples. However, the present invention is not limited to the following examples. In the table below, sample numbers marked with * are comparative examples.

[0072] Experiment 1 In experiment 1, soft magnetic alloy powder was produced by gas atomization. In gas atomization, the molten metal injection temperature was set to 1500°C, the molten metal injection rate was set to 1.2 kg / min, the high-pressure gas pressure was set to 7.0 MPa, and the cooling water pressure was set to 10 MPa, and soft magnetic alloy powder with an average particle size (D50) based on volume in the range of 15 to 30 μm was obtained. Then, the soft magnetic alloy powder was subjected to heat treatment under the conditions shown in Table 1 to obtain soft magnetic alloys according to samples 2 to 5 and 7 to 16. In addition, in experiment 1, soft magnetic alloys according to samples 1 and 6 that were not subjected to heat treatment were also produced, and the following evaluations were performed based on sample 1 or sample 6.

[0073] <Composition and crystal structure of soft magnetic alloy powder> The composition of the soft magnetic alloy powder obtained by the gas atomization method was measured by ICP. As a result, in samples 1 to 5 in Experiment 1, the soft magnetic alloy powder (i.e., the inner region 2) was composed of Fe 0.7 Co 0.3 On the other hand, in the samples 6 to 16 in the experiment 1, the soft magnetic alloy powder (i.e., the inner region 2) had the average composition represented by the formula: (Fe 0.7 Co 0.3 ) 0.82 B 0.11 P 0.02 S 0.03 C 0.01 Cr 0.01It was confirmed that the alloy composition satisfies the following atomic ratios: α = 0.300, β = 0, γ = 0, a = 0.110, b = 0.020, c = 0.030, d = 0.010, e = 0.010.

[0074] In addition, when X-ray crystal structure analysis was performed on the soft magnetic alloy powder of Experiment 1 by XRD, it was confirmed that the soft magnetic alloy powder (i.e., inner region 2) of Samples 1 to 5 of Experiment 1 was crystalline with an amorphization degree X of less than 85%. On the other hand, it was confirmed that the soft magnetic alloy powder (i.e., inner region 2) of Samples 6 to 16 of Experiment 1 was amorphous with an amorphization degree X of 85% or more.

[0075] <Analysis of surface structure> For each soft magnetic alloy sample in Experiment 1, a thin slice sample was taken near the surface by a microsampling method using an FIB. Then, using the thin slice sample, a mapping analysis was performed by TEM-EDX to investigate the presence or absence of Co-enriched regions 11 (P-enriched regions 11a and Co-enriched regions 11b). In addition, a component analysis was performed in a specific region by TEM-EELS to measure the degree of Co enrichment in the Co-enriched regions 11. The analysis results of the surface layer structure are shown in Table 1. The EELS analysis confirmed that the Co-enriched regions 11 were an amorphous metal phase.

[0076] <Saturation magnetic flux density Bs> The Bs of the soft magnetic alloys of each sample was measured using a vibrating sample magnetometer (VSM) under a magnetic field of 1000 kA / m. The measurement results are shown in Table 1. Regarding Bs, a value of 1.50 T or more was judged to be good, and a value of 1.70 T or more was judged to be even better.

[0077] <Water immersion test> First, before conducting the water immersion test, magnetic core samples were prepared using the soft magnetic alloys of each specimen. The magnetic core samples were prepared according to the following procedure. Granules were obtained by mixing 100 parts by mass of the soft magnetic alloy with 3 parts by mass of epoxy resin. The granules were then filled into a mold and subjected to a pressure of 4 ton / cm. 2The magnetic core sample was pressed at a pressure of 1.0 mm to obtain a toroidal magnetic core sample having an outer diameter of 11 mm, an inner diameter of 6.5 mm, and a height of 1.0 mm.

[0078] A water immersion test was conducted to evaluate the corrosion resistance of the magnetic core samples obtained above. In the water immersion test, the magnetic core samples were immersed in tap water, and the time until rust was visually observed (rust onset time) was measured. In experiment 1, the rust onset time T1 of sample 1 or sample 6, which had not been subjected to heat treatment, was used as the standard to evaluate the corrosion resistance of each sample. Specifically, in experiment 1, samples whose rust onset time was less than 1.2 times T1 (rust onset time of sample 1 or sample 6) were judged as "F (fail)", and samples whose rust onset time was 1.2 times or more than T1 were judged as "G (good)". The results of the two-level evaluation based on "F, G" are shown in Table 1.

[0079] [Table 1]

[0080] As shown in Table 1, it was confirmed that the samples (3 to 5, 8 to 16) in which the Co-enriched region 11 was formed and the Co enrichment degree exceeded 1.20 had relatively good corrosion resistance compared to the reference alloy (sample 1 or sample 6). It was also confirmed that the perpendicular distance d1 from the outermost surface 10 to the Co-enriched region 11 was 30 nm or less in samples 3 to 5 and 8 to 16. From these results, it was proven that by forming the Co-enriched region 11 having predetermined characteristics on the surface side of the soft magnetic alloy, it is possible to improve the corrosion resistance while maintaining a high Bs.

[0081] Although specific values ​​for the time to rust formation are omitted in Table 1, it was confirmed that the higher the Co concentration, the better the corrosion resistance relative to the reference alloy tends to be.

[0082] Experiment 2 In experiment 2, the alloy composition was changed to obtain soft magnetic alloys according to samples 2-1 to 2-90. The alloy composition of each sample analyzed by ICP is shown in Tables 2 to 7.

[0083] Specifically, in samples 2-1 to 2-14 shown in Table 2, the composition formula: (Fe 1-α Co α ) 0.84 B 0.11 S 0.03 C 0.01 Cr 0.01 While satisfying the conditions (atomic ratios: β=0, γ=0, a=0.110, b=0, c=0.030, d=0.010, e=0.010), soft magnetic alloys were prepared by changing the Co atomic ratio α.

[0084] In addition, for samples 2-15 to 2-34 shown in Table 3, the atomic ratios of Co, Ni, and X1 were fixed at α = 0.300, β = 0, and γ = 0, and the atomic ratios of metalloids (B, P, Si, C) and Cr were changed to produce soft magnetic alloys.

[0085] In addition, in samples 2-35 to 2-38 shown in Table 4, the composition formula: (Fe (1-(0.3+β) Co 0.3 Ni β ) 0.84 B 0.11 S 0.03 C 0.01 Cr 0.01 While satisfying the conditions (atomic ratios: α = 0.300, γ = 0, a = 0.110, b = 0, c = 0.030, d = 0.010, e = 0.010), soft magnetic alloys were prepared by changing the atomic ratio β of Ni.

[0086] In addition, in samples 2-39 to 2-90 shown in Tables 5 to 7, the composition formula ((Fe 0.7 Co 0.3 ) 0.975 X1 0.025 ) 0.84 B 0.11 S 0.03 C 0.01 Cr 0.01 While satisfying the following criteria (atomic ratio: α = 0.300, β = 0, γ = 0.025, a = 0.110, b = 0, c = 0.030, d = 0.010, e = 0.010), a soft magnetic alloy was prepared by changing the element type of X1.

[0087] It was confirmed that the degree of amorphousness X of each soft magnetic alloy in Experiment 2 was 85% or more. In Experiment 2, samples with and without a prescribed heat treatment were prepared for each alloy composition, and in Tables 2 to 7, the samples with and without heat treatment are indicated as "Y" and "N", respectively. The heat treatment conditions in Experiment 2 were as follows: holding temperature: 200°C, holding time: 1 h, oxygen concentration in the heating furnace: 100 ppm, and gauge pressure in the heating furnace: 0.30 kPa.

[0088] In addition, for each of the samples 2-1 to 2-90 in the experiment 2, the measurement of Bs and the water immersion test were carried out in the same manner as in the experiment 1. In the water immersion test in the experiment 2, the rust formation time T N Based on the standard, the time to rust on the heat-treated sample was T Y As, T Y / T N Samples with a score of <1.2 were classified as "F (fail)" and samples with a score of 1.2 or less were classified as "T Y / T N The samples for which this was the case were judged to be "G (good)." The evaluation results are shown in Tables 2 to 7.

[0089] [Table 2]

[0090] [Table 3]

[0091] [Table 4]

[0092] [Table 5]

[0093] [Table 6]

[0094] [Table 7]

[0095] As shown in Tables 2 to 7, the samples that underwent the prescribed heat treatment had higher corrosion resistance than the samples that did not undergo heat treatment. This result shows that, within the range of the alloy composition shown in Experiment 2, it is possible to improve corrosion resistance while maintaining a high Bs by forming Co-enriched region 11 (P-enriched region 11a and Co-enriched region 11b) having prescribed characteristics.

[0096] In addition, to add a supplement to the results in Table 2, the rust generation time tended to be longer as the Co content in the inner region 2 (i.e., the Co content of the soft magnetic alloy) increased. In other words, the corrosion resistance as an absolute evaluation increased as the Co content in the inner region 2 increased. However, as shown in sample 2-14 in Table 2, when the Co content in the inner region 2 was high, the Co enrichment degree tended to be warped and reduced. In addition, the relative corrosion resistance improvement effect (i.e., corrosion resistance relative to the reference alloy) was better in other samples 2-2, 4, 6, 8, 10, and 12, which had a higher Co enrichment degree, than in sample 2-14. In other words, from this result, it was confirmed that the higher the Co enrichment degree, the greater the tendency for the improvement effect of corrosion resistance relative to the reference alloy (a sample that was not subjected to heat treatment to form an enriched region) to be.

[0097] Experiment 3 In Experiment 3, amorphous soft magnetic alloy powders with an amorphous degree X of 85% or more (samples 3-1 and 3-2), nanocrystalline soft magnetic alloy powders with an amorphous degree X of less than 85% (samples 3-3 and 3-4), and crystalline soft magnetic alloy powders with an amorphous degree X of less than 85% (samples 3-5 and 3-6) were produced to investigate the effect of differences in the crystal structure of the soft magnetic alloys on corrosion resistance.

[0098] In Experiment 3, the crystal structure of each sample was controlled by a pre-processing heat treatment. Specifically, in Samples 3-1 and 3-2 in Experiment 3, the pre-processing heat treatment was not performed, and thus amorphous soft magnetic alloy powder was obtained. Samples 3-1 and 3-2 correspond to Samples 6 and 14 in Experiment 1. In addition, in Samples 3-3 and 3-4 in Experiment 3, the pre-processing heat treatment was performed at a holding temperature of 500°C, and thus nanocrystalline soft magnetic alloy powder was obtained. In addition, in Samples 3-5 and 3-6 in Experiment 3, the pre-processing heat treatment was performed at a holding temperature of 650°C, and thus crystalline soft magnetic alloy powder was obtained. In addition, other conditions in the above pre-processing heat treatment were a heating rate of 100°C / min, an atmosphere in the furnace: an Ar atmosphere, and a gauge pressure in the heating furnace: 0.0 kPa, and the crystal structure was controlled in a state in which the Co-enriched region 11 was not formed.

[0099] The composition of the soft magnetic alloys in each sample in Experiment 3 was (Fe 0.7 Co 0.3 ) 0.82 B 0.11 P 0.02 S 0.03 C 0.01 Cr 0.01 The same is true for all samples. In experiment 3, samples were prepared for each crystal structure, with and without heat treatment, and in Table 8, the samples with heat treatment are indicated as "Y" and those without heat treatment are indicated as "N." In addition, for samples (3-4 and 3-5) that were subjected to the pre-process heat treatment, the heat treatment for forming the Co-enriched region 11 was performed after the pre-process heat treatment. The conditions for the heat treatment in experiment 3 were a holding temperature of 200°C, a holding time of 1.0 h, an oxygen concentration in the heating furnace of 100 ppm, and a gauge pressure in the heating furnace of 0.3 kPa.

[0100] In Experiment 3, Bs measurement and water immersion test were performed in the same manner as in Experiment 2. In the water immersion test in Experiment 3, the rust formation time T N Based on the standard, the time to rust on the heat-treated sample was T Y As, T Y / T NSamples with a score of <1.2 were classified as "F (fail)" and samples with a score of 1.2 or less were classified as "T Y / T N The samples for which the results were as follows were judged to be "G (good)." The evaluation results of Experiment 3 are shown in Table 8.

[0101] [Table 8]

[0102] As shown in Table 8, even in the case of nanocrystalline or crystalline soft magnetic alloys, it was found that, as in the case of amorphous alloys, samples 3-4 and 3-6 in which the Co-enriched region 11b was formed by a predetermined heat treatment had improved corrosion resistance compared to samples 3-3 and 3-5 in which no heat treatment was performed. In addition, when the results of samples 3-3 to 3-5 shown in Table 8 are compared with the results of samples 3-1 and 3-2, it was found that when the soft magnetic alloy is amorphous, the rusting time is longer than that of the reference alloy, and the relative improvement effect of corrosion resistance is particularly good.

[0103] Experiment 4 In experiment 4, ribbon-shaped soft magnetic alloy samples (samples 4-1 and 4-2) were produced by the single roll method. The ribbon production conditions were: temperature of molten metal sprayed onto the roll: 1300°C, roll temperature: 30°C, roll rotation speed: 25 m / sec. The atmosphere inside the chamber was air. The soft magnetic alloy ribbon obtained under the above conditions had a thickness of 20 to 25 μm, a width in the short direction of about 5 mm, and a ribbon length of about 10 m.

[0104] In addition, in Experiment 4, similarly to Experiment 1, the alloy compositions of Samples 4-1 and 4-2 were measured by ICP. 0.7 Co 0.3 ) 0.82 B 0.11 P 0.02 S 0.03 C 0.01 Cr 0.01(Atomic ratio; α=0.300, β=0, γ=0, a=0.110, b=0.020, c=0.030, d=0.010, e=0.010) was satisfied. Furthermore, when the crystal structures of the soft magnetic alloy ribbons according to Samples 4-1 and 4-2 were measured by XRD, it was confirmed that both were amorphous with an amorphization degree X of 85% or more.

[0105] The soft magnetic alloy ribbon of Sample 4-1 was subjected to surface structure analysis, Bs measurement, and water immersion test without heat treatment. On the other hand, the soft magnetic alloy ribbon of Sample 4-2 was subjected to heat treatment under the conditions shown in Table 9, and then the same evaluation as Sample 4-1 was performed. In the water immersion test of the soft magnetic alloy ribbon, the ribbon was cut into an arbitrary size (length about 4 cm × width about 5 mm) to prepare a test sample, and the ribbon-shaped test sample was immersed in tap water. The method of pass / fail judgment in Experiment 4 was the same as in Experiment 1. The evaluation results of each sample in Experiment 4 are shown in Table 9. Table 9 also shows the experimental results of soft magnetic alloy powders (samples 6 and 14 in Experiment 1) having the same alloy composition as Samples 4-1 and 4-2.

[0106] [Table 9]

[0107] As shown in Table 9, it was confirmed that even when the soft magnetic alloy has a ribbon shape, by forming the Co-enriched regions 11b by a predetermined heat treatment, it is possible to improve the corrosion resistance while maintaining a high Bs. [Explanation of symbols]

[0108] 1,1a,1b … Soft magnetic alloy 2 … Internal area 10 … Top surface 11… Co-enriched region 12 ... SB oxide layer 13 … Fe oxide layer 20 … Covering layer

Claims

1. an inner region having a soft magnetic alloy composition including Fe and Co; A Co-enriched region is present on the surface side of the inner region and has a higher Co concentration than the inner region, The Co concentration in the Co-enriched region is 1.25 or more, A soft magnetic alloy in which the content of Co relative to the total amount of Fe, Co and Ni is 30% or more and 70% or less on an atomic number basis.

2. 2. The soft magnetic alloy according to claim 1, wherein the Co-enriched regions are metallic phases.

3. 3. The soft magnetic alloy according to claim 1, wherein the degree of amorphousness is 85% or more.

4. The soft magnetic alloy according to any one of claims 1 to 3, which is in the form of a ribbon.

5. The soft magnetic alloy according to any one of claims 1 to 3, which is in the form of a powder.

6. A magnetic component comprising the soft magnetic alloy according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Amorphous soft magnetic alloy, amorphous soft magnetic alloy member, amorphous soft magnetic alloy ribbon, amorphous soft magnetic alloy powder and magnetic core and inductance component using the same

    JP2007231415A

  • Highly corrosion-resistant amorphous alloy

    JP2009293099A

  • Amorphous alloy powder, dust core, magnetic element and electronic apparatus

    JP2014167139A

  • Soft magnetic alloy and magnetic component

    JP2019131853A

  • Fe-BASED SOFT MAGNETIC ALLOY RIBBON AND MAGNETIC CORE COMPRISING SAME

    WO2016104000A1